Industry 4.0 and Industry 5.0—Inception, Conception, Perception, and Rethinking Loyalty Employment - Khuzaini; Irpan, M; Shaddiq, Syahrial (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
This paper delves into the transformative journey of Industry 4.0 and explores the emerging landscape of Industry 5.0. Beginning with the inception of Industry 4.0, characterized by the integration of digital technologies and automation in manufacturing, the paper traces the evolution of smart factories and interconnected systems. It examines the conception of Industry 4.0, highlighting key technologies such as the Internet of Things (IoT), artificial intelligence (AI), and big data analytics that have reshaped industrial processes. Moving forward, the paper explores the perception of Industry 4.0, shedding light on its impact on production efficiency, supply chain management, and overall business operations. It discusses the challenges faced during the adoption of Industry 4.0 and emphasizes the paradigm shift towards data-driven decision-making. As the industrial landscape evolves, the paper anticipates the advent of Industry 5.0, focusing on human-machine collaboration and a more holistic approach to manufacturing. It examines the conception of Industry 5.0, emphasizing the integration of human-centric values, creativity, and adaptability in the production processes. In the context of this industrial revolution, the paper also addresses the rethinking of employment loyalty. It analyzes the changing dynamics of the workforce, emphasizing the need for upskilling and adaptability in the face of automation and technological advancements. The discussion extends to the role of employers in fostering a culture of continuous learning and employee engagement to ensure loyalty in the evolving industrial landscape. In conclusion, this paper provides a comprehensive overview of the inception, conception, and perception of Industry 4.0, while also anticipating the paradigm shift towards Industry 5.0. It underscores the importance of rethinking employment loyalty in the context of evolving technologies, emphasizing the symbiotic relationship between human creativity and technological innovation